National implementation of the SIDS/POA : a Caribbean perspective. - UN ECLAC (UN ECLAC, 2011)
Attempts to present a clear picture of where the Caribbean is now in terms of SIDS/POA implementation and the future actions that will be pursued.
Keywords: SMALL STATES; SUSTAINABLE DEVELOPMENT; CLIMATE CHANGE; DISASTERS; WASTE MANAGEMENT; MARINE RESOURCES; ENERGY RESOURCES; TOURISM; BIODIVERSITY; TECHNICAL COOPERATION; TRANSPORT; COMMUNICATION; SCIENCE AND TECHNOLOGY; HUMAN RESOURCES DEVELOPMENT; CARIBBEAN